Obhajoba oprávněného vzdoru vůči svrchovaným vládcům v díle Christophera Goodmana - Miroslav Beneš (Theatrum Historiae)
Christopher Goodman was a famous English 16th century reformer, a colleague and a close friend of John Knox, Father of Scottish Presbyterian Church. Christopher Goodman was well-known thanks to his critical work ’How Superior Powers Ought to Be Obeyed by Their Subjects and Wherein They May Lawfully by God’s Word Be Disobeyed and Resisted’. John Knox and Christopher Goodman were the most critical authors of their age. However, Goodman’s radical way of thinking was stronger than Knox’s and that was the reason for the prohibition of his book.